2014
DOI: 10.1186/1472-6882-14-116
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor pharmacological evaluation of extracts from stellera chamaejasme L based on hollow fiber assay

Abstract: BackgroundStellera chamaejasme L, a traditional Chinese herb, has long been used for treatment of various tumors in the Chinese population. In our previous study, we paid an attention to the cytotoxic and proapoptotic effects of Stellera chamaejasme L extracts (ESC, ESC-1 and ESC-2, the latter two were isolated from ESC) on 4 various tumor cells (NCI-H157, NCI-H460, BEL-7402 and SK-HEP-1) in vitro. ESCs showed significantly inhibitory effects on the 4 tumor cells. ESC-2 had the strongest inhibitory effect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Many studies showed that a variety of Stellera chamaejasme L. extracts or monomers had anti-tumor activities and could induce apoptosis of tumor cells [ 7 10 ]. Our previous studies also got the same results [ 11 , 12 ], but there were no experiments on its anti-metastasis effects. In this study, we further observed the effects of ESC on TGF-β-mediated EMT and classical Smad-dependent signaling pathway in HepG2 liver cancer cells.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Many studies showed that a variety of Stellera chamaejasme L. extracts or monomers had anti-tumor activities and could induce apoptosis of tumor cells [ 7 10 ]. Our previous studies also got the same results [ 11 , 12 ], but there were no experiments on its anti-metastasis effects. In this study, we further observed the effects of ESC on TGF-β-mediated EMT and classical Smad-dependent signaling pathway in HepG2 liver cancer cells.…”
Section: Introductionsupporting
confidence: 61%
“…ESC, the extract of Stellera Chamaejasme L., inhibited proliferation and induced apoptosis in various tumor cells by activation apoptotic death receptor signaling pathway in our previous researches [ 11 , 12 ]. In this study, we found that EMT induced by TGF-β in HepG2 cells could be reversed by ESC (doses less than 12.5 μg/mL were used to avoid the influence of anti-proliferation of ESC).…”
Section: Discussionmentioning
confidence: 99%
“…Compounds obtained from S. chamaejasme L. have shown significant anticancer activities (Li, Zhang, Pang, Zheng, & Gan, 2014;Liu et al, 2014;Qian & Li, 2017). Isochamaejasmin induces apoptosis in leukemia cells by inhibiting the activity of Bcl-2 family proteins (Zhang, Abbreviations: AUC, area under the plasma concentration-time curve; C max , Maximum plasma concentration; MRT, mean residence time; QC, quality control; RE, relative error; RSD, relative standard deviation; t 1/2 , half-life; T max , time to C max ; UPLC-MS/MS, ultra-performance liquid chromatographytandem mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies of S. chamaejasme L. have shown that it contains various kinds of chemical components, including diterpene, lignans, coumarins, phenylpropanoid, flavonoids and volatile oil (Li, Shen, Bao, Chen, & Li, ; Yan et al, ; Zhang et al, ). Modern studies have suggested that flavonoids from S. chamaejasme L. are the main components that mostly contribute to the pharmacological efficacy (Liu et al, ; Liu & Zhu, ; Liu, Han, et al, ; Liu, Yang, et al, ), such as anti‐cancer activity (Liu et al, ; Li, Zhang, Pang, ZhengChen, & Gan, ), anti‐fatty liver (Wang, Li, Han, Wang, & Li, ) and anti‐HIV (Asada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…. Modern studies have suggested that flavonoids from S. chamaejasme L. are the main components that mostly contribute to the pharmacological efficacy Liu, Han, et al, 2014;Liu, Yang, et al, 2014), such as anti-cancer activity Li, Zhang, Pang, ZhengChen, & Gan, 2014), anti-fatty liver (Wang, Li, Han, Wang, & Li, 2015) and anti-HIV (Asada et al, 2013). effects.…”
mentioning
confidence: 99%